2016
DOI: 10.2147/opto.s116535
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and degrees of myopia and hyperopia at Gondar University Hospital Tertiary Eye Care and Training Center, Northwest Ethiopia

Abstract: BackgroundRefractive errors are the second and third leading cause of visual impairment and blindness in Ethiopia, respectively. The situation is worse where accessing spectacles, which are the only management option in developing countries, is a major issue. Gondar University Hospital Tertiary Eye Care and Training Center is the only referral eye care center, and it lacks published evidence on the prevalence and degrees of refractive errors (myopia and hyperopia).ObjectiveThe purpose of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…Different methods and population studied may be responsible for the difference in association between refractive error and gender. 485(89.3%) individuals had low hypermetropia, similar results were reported by Alemu et al 31 (low hyperopia 86% as compared to high hyperopia 4.5%) and Raju et al 9 In our study, 176(73.3%) of individuals out of 240 were having low astigmatism. Similar results were reported by Raju et al 9 (low astigmatism 54.78%) and Abdullah et al which showed that low astigmatism was the most prevalent astigmatic error.…”
Section: Discussionsupporting
confidence: 90%
“…Different methods and population studied may be responsible for the difference in association between refractive error and gender. 485(89.3%) individuals had low hypermetropia, similar results were reported by Alemu et al 31 (low hyperopia 86% as compared to high hyperopia 4.5%) and Raju et al 9 In our study, 176(73.3%) of individuals out of 240 were having low astigmatism. Similar results were reported by Raju et al 9 (low astigmatism 54.78%) and Abdullah et al which showed that low astigmatism was the most prevalent astigmatic error.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies across the world have reported the prevalence of refractive errors as an index of descriptive epidemiology, and it may be the only field in refractive errors which includes reports from almost every corner of the world. 2 , 3 , 4 , 8 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 78 , 79 , 80 , 81 , 82 , 83 ,…”
Section: Discussionmentioning
confidence: 99%
“…About 942 articles were excluded due to duplication, 493 articles were excluded due to different in study context, 13 , 14 , 15 , 16 , 17 10 articles were excluded due to different in interest of outcome 18 , 19 , 20 , 21 , 22 , 23 , 24 and 5 articles were excluded due to different in study population. 25 , 26 Finally, 12 cross-sectional studies were identified as having the potential to be included in the current systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%